2020
DOI: 10.1007/s00276-020-02551-2
|View full text |Cite
|
Sign up to set email alerts
|

The additional role of virtual to traditional dissection in teaching anatomy: a randomised controlled trial

Abstract: Introduction Anatomy has traditionally been taught via dissection and didactic lectures. The rising prevalence of informatics plays an increasingly important role in medical education. It is hypothesized that virtual dissection can express added value to the traditional one. Methods Second-year medical students were randomised to study anatomical structures by virtual dissection (intervention) or textbooks (controls), according to the CONSORT guidelines. Subsequently, they applied to the corresponding gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 29 publications
0
50
0
3
Order By: Relevance
“…In cases where F2F education cannot be continued, the anatomists around the world is looking into powerful innovative alternatives to minimize these negative effects on students. Studies have revealed that students who apply traditional dissection in combination with virtual dissection have shown a significant improvement in learning outcomes [ 3 ]. In our study, the questions that make comparisons between anatomy and other basic science courses indicate that one of the most difficult lessons to learn through distance medical education is anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where F2F education cannot be continued, the anatomists around the world is looking into powerful innovative alternatives to minimize these negative effects on students. Studies have revealed that students who apply traditional dissection in combination with virtual dissection have shown a significant improvement in learning outcomes [ 3 ]. In our study, the questions that make comparisons between anatomy and other basic science courses indicate that one of the most difficult lessons to learn through distance medical education is anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaver training, in this digital scenario with the rise in the prevalence of informatics, remains the mainstay in anatomy teaching, albeit fueling a continuous debate on its use in teaching ( 16 , 17 ). Comprehensive software with deep learning and artificial intelligence technologies may have a rising role in medical education, being an integrative tool to combine with the human cadaver dissection ( 18 ). Moreover, in the COVID-19 pandemic age, Ross et al ( 19 ) underlined that teaching anatomy with dissection is essential and possible.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the training of medical students in discipline independent skills or humanistic skills have also suffered. Although human dissection is associated with inherent drawbacks and educators have suggested effective replacements [2,4], nevertheless as educators it is pertinent to realize that a compromise in terms of desirable outcome of dissection-based learning during COVID-19 pandemic can adversely affect the eventual fabric of the medical students when they are licensed to undertake medical practice [9]. Hence judicious analysis of the current situation and logical remedial measures are needed to minimize the process of attrition.…”
Section: Shortfall Of Physical Human Dissection Sessions During Covid-19 Pandemic (Problem Statement)mentioning
confidence: 99%